Outcomes of Patients With Esophageal Cancer Staged With [(18)F]Fluorodeoxyglucose Positron Emission Tomography (FDG-PET): Can Postchemoradiotherapy FDG-PET Predict the Utility of Resection? - Monjazeb, Arta Monir (American Society of Clinical Oncology, 2010)
PURPOSE: To determine whether [(18)F]fluorodeoxyglucose positron emission tomography (FDG-PET) can delineate patients with esophageal cancer who may not benefit from esophagectomy after chemoradiotherapy. PATIENTS AND METHODS: We reviewed records of 163 patients with histologically confirmed stage I to IVA esophageal cancer receiving chemoradiotherapy with or without resection with curative intent. All patients received surgical evaluation. Initial and postchemoradiotherapy FDG-PET scans and prognostic/treatment variables were analyzed. FDG-PET complete response (PET-CR) after chemoradiotherapy was defined as standardized uptake value ≤ 3. RESULTS: Eighty-eight patients received trimodality therapy and 75 received chemoradiotherapy. Surgery was deferred primarily due to medical inoperability or unresectable/metastatic disease after chemoradiotherapy. A total of 105 patients were evaluable for postchemoradiotherapy FDG-PET response. Thirty-one percent achieved a PET-CR. PET-CR predicted for improved outcomes for chemoradiotherapy (2-year overall survival, 71% v 11%, P < .01; 2-year freedom from local failure [LFF], 75% v 28%, P < .01), but not trimodality therapy. On multivariate analysis of patients treated with chemoradiotherapy, PET-CR is the strongest independent prognostic variable (survival hazard ratio [HR], 9.82, P < .01; LFF HR, 14.13, P < .01). PET-CR predicted for improved outcomes regardless of histology, although patients with adenocarcinoma achieved a PET-CR less often. CONCLUSION: Patients treated with trimodality therapy found no benefit with PET-CR, likely because FDG-PET residual disease was resected. Definitive chemoradiotherapy patients achieving PET-CR had excellent outcomes equivalent to trimodality therapy despite poorer baseline characteristics. Patients who achieve a PET-CR may not benefit from added resection given their excellent outcomes without resection. These results should be validated in a prospective trial of FDG-PET–directed therapy for esophageal cancer.